Gender role conflict and sexual health and relationship practices amongst young men living in urban informal settlements in South Africa. Issue 1 (2nd January 2020) - Closson, Kalysha; Hatcher, Abigail; Sikweyiya, Yandisa; Washington, Laura; Mkhwanazi, Smanga; Jewkes, Rachel; Dunkle, Kristin; Gibbs, Andrew
Abstract: Qualitative research suggests that men's inability to achieve dominant forms of masculinity may be related to HIV-risk behaviours and intimate partner violence (IPV) perpetration. Using clustered cross-sectional data, we assessed how young men's gender role conflict was associated with HIV-risk behaviours in urban informal settlements in KwaZulu-Natal, South Africa. Gender Role Conflict and Stress (GRC/S) was measured using a South African adaptation of the GRC/S scale comprising three sub-scales: subordination to women; restrictive emotionality; and success, power and competition. In random-effect models adjusting for socio-demographics, we tested the relationship with GRC/S sub-scales and sexual health behaviours (transactional sex, use of sex workers, ≥2 main partners and ≥2 casual/once off partners), and relationship practices (relationship satisfaction, relationship control, partnership type and perpetration of IPV). Overall, 449 young men (median age = 25, Q1, Q3 = 23–28) were included in the analysis. Higher GRC/S scores, denoting more GRC/S, were associated with increased relationship control and increased odds of having ≥2 casual or one-off partners and engaging in transactional sex. We found differences in associations between each sub-scale and sexual health and relationship practices, highlighting important implications for informing both theoretical understandings of masculinity and gender transformative efforts.